(–)-Epicatechin Supplementation Inhibits Aerobic Adaptations to Cycling Exercise in Humans - Schwarz, Neil A.; Blahnik, Zachary J.; Prahadeeswaran, Srihari; McKinley-Barnard, Sarah K.; Holden, Shelley L.; Waldhelm, Andy (Frontiers in Nutrition, 2018)
The purpose of the study was to determine if cycling exercise combined with (-)-epicatechin supplementation was more effective at increasing training adaptations than cycling combined with placebo. Blood and muscle samples were obtained at rest before and after training to determine effects of (-)-epicatechin supplementation on total serum antioxidant capacity, skeletal muscle mitochondrial protein content, and skeletal muscle myostatin gene expression. Participants (n= 20) completed two testing sessions separated by four weeks of cycle training with twice daily supplementation of 100 mg (200 mg total daily) of (-)-epicatechin or placebo. Data were analyzed using a two-way mixed model ANOVA for each variable and alpha level was set at p ≤ .05. A significant increase was observed for time for relative peak anaerobic power (p < .01), relative anaerobic capacity (p < .01), and fatigue index (p < .01). A significant increase was observed for time for absolute peak VO2 (p < .01) and peak power output obtained during the peak VO2 test (p < .01). A significant interaction between group and time for relative peak VO2 was observed (p = .04). Relative peak VO2 significantly increased over time in the placebo group (p < .01), but not in the (-)-epicatechin group (p = .21). A significant increase was observed for time for total serum antioxidant capacity (p = .01). No interaction or main effect of time was observed for myostatin (p > .05). Likewise, no interaction or main effect of time was observed for cytochrome C or citrate synthase (p > .05). A significant interaction effect was observed for succinate dehydrogenase (SDH; p = .02). SDH content increased significantly for the placebo group (p = .03, partial η2 = .59), but not the (-)-epicatechin group (p = .81). Further, whereas no difference existed between groups for SDH at baseline (p = .23), SDH content was significantly greater in the placebo group at the post time point (p = .01). Results indicate that (-)-epicatechin supplementation does not affect myostatin gene expression or anaerobic training adaptations, but inhibits aerobic and mitochondrial SDH adaptations to cycle exercise training.